Ekaristi, Epiclesis, dan Anamnesis Menurut Michael Welker dan Alexander Schmemann sebagai Diskusi Oikumenis Reformed dengan Ortodoks Timur - Jeconiah Lunardi; Billy Kristanto (Verbum Christi: Jurnal Teologi Reformed Injili, 2022)
This paper’s aims to show that the ecumenical spirit in Eucharist is right, based on the Bible, church’s doctrine of Reformed tradition and Eastern Orthodox tradition. By conducting a literature study to compare the thoughts of two theologians from the two traditions, namely Michael Welker and Alexander Schmemann, this study has found that the Holy Communion  unified the vertical dimension and the horizontal dimension which makes God’s people from all ages and places united as a holy and universal church, and  with the presence of Christ in every Holy Communion.